The Impact of UTAUT Model and ICT Theoretical Framework on University Academic Staff: Focus on Adamawa State University, Nigeria. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
This paper examined the impact of UTAUT model and ICT theoretical framework on university academicians. The UTAUT model theory was verified using multiple regressions of the four constructs on behavioral intention to accept and use ICT by the Adamawa State University (ADSU) academic staff. The ICT theoretical framework reveals the connectivity between education and the independent variables, use of ICT, ICT infrastructure, staff development and ICT available tools as it brings transformation in education. We have verified the influence of the four UTAUT constructs on the behavioral intention of the university academicians towards the acceptance and use of ICT for teaching and learning. The UTAUT constructs significantly correlated with behavioral intention to use ICT. These are the factors associated with ICT acceptance and usage in Adamawa State University. According to our results Perceived Usefulness (PU) has R2 = .181 and significant with p-value .047(model 1), and Perceived ease of use (PEOU), has R2 = .270, significant with p-vale .000 (model 10). This has answered objective 1, which is to examine the factors associated with ICT acceptance and usage in (ADSU). The study confirms that the most influential UTAUT constructs influencing the behavioral intention of the academic staff to accept and use ICT is Effort expectancy (EE) in (ADSU)(model 10), with R= .519 and R2 = .270 ( Answered Objective 2). This study confirms the validity of the UTAUT model in the field context of a developing country‟s educational system. Knowledge gained from the study is beneficial to both the university academic staff and the ICT policy makers in developing countries.